The triglyceride-to-high-density lipoprotein cholesterol ratio is associated with an increased risk of peripartum cardiomyopathy - Chen, Naiyi; Xiao, Jie; Luo, Yijie; Fu, Kang; Sun, Ziru; Zhang, Xinyu; Liu, Yanan; Lu, Huixia; Ji, Xiaoping (Frontiers in Endocrinology, 2024)
Background: Peripartum cardiomyopathy (PPCM) is a form of heart failure that severely affects women during the late stages of pregnancy and in the postpartum period. Currently, the diagnosis of PPCM is not fully understood and is likely multifactorial. Abnormal lipid metabolism plays an important role in the onset of cardiovascular diseases, especially in patients with heart failure. Moreover, animal experiments have confirmed a possible association between abnormal lipid metabolism and PPCM onset. However, clinical evidence is currently lacking, and reliable and effective indicators for predicting the onset of PPCM are insufficient. The ratio of triglyceride to high-density lipoprotein cholesterol (TG/HDL-C) is a novel metabolic marker that is associated with the risk of coronary heart disease. However, the relationship between the TG/HDL-C ratio and the risk of PPCM in parturients remains unknown. Therefore, this study aimed to explore the role of the TG/HDL-C ratio in predicting the risk of PPCM.Methods: This study included 600 parturients hospitalized at Qilu Hospital of Shandong University between January 2010 and August 2023 (150 patients with PPCM and 450 healthy parturients). The TG/HDL-C ratio was calculated as triglyceride levels (mmol/L)/high-density lipoprotein cholesterol levels (mmol/L). The relationship between the TG/HDL-C ratio and PPCM was analyzed using logistic regression analysis and receiver operating characteristic curve analysis. Results: Significant differences were observed in the TG/HDL-C ratios between patients with PPCM and healthy parturients. The TG/HDL-C ratio was higher in patients with PPCM than in healthy parturients (P<0.001). Logistic regression analysis revealed that the TG/HDL-C ratio increased the risk of PPCM and had predictive accuracy for the onset of PPCM (Odds ratio, 1.249; 95% confidence interval, 1.004-1.553; P=0.046). Moreover, the TG/HDL-C ratios were positively correlated with the NT-proBNP levels at the onset of PPCM (R 2 =0.081, P=0.008).Conclusions: A higher TG/HDL-C ratio was significantly associated with the risk of PPCM.